Alkali-Activation of Synthetic Aluminosilicate Glass With Basaltic Composition - Alzeer, Mohammad I. M.; Nguyen, Hoang; Cheeseman, Christopher; Kinnunen, Paivo (Frontiers in Chemistry, 2021)
Alkali-activated materials (AAMs) are a potential alternative to Portland cement because they can have high strength, durability and low environmental impact. This paper reports on the structural and mechanical characteristics of aluminosilicate glass with basalt-like compositions, as a feedstock for AAMs. The alkali-activation kinetics, microstructure and mechanical performance of the AAMs formed were investigated. The results show that AAMs prepared from basalt glass have high compressive strength compared to those made using metakaolin or granulated blast furnace slag. The glass can be formed from carbonate-free and abundant natural resources such as basalt rocks or mixtures of silicate minerals.